Ethnobotany of Indigofera in Indonesia - MUZAYYINAH, MUZAYYINAH (Department of Biology Education Faculty of Teacher Training and Education Sebelas Maret Un, 2016)
Tom-toman (Indigofera) plants are popular among batik and weavers' community in Indonesia for long time ago as one of natural dyes. The etnobotany of Indigofera need to be analyzed by considering the indigenous knowledge of people who know and utilize the plants since ancient period, and passed the knowledge from their ancestors. This study aims to explore information of etnobotany of Indigofera in the world and particularly in Indonesia. The information of its botany found from old manuscripts and literatures, which furtherly compared with morpohologycal observation. Some samples of Indigofera found in Flores and Java were determined, and matched with the characteristics that had been released by several well-known botanists. It can be said that indigenous people had developed adequate skills on how to name the plants, distinguish the species, and utilize for daily purposes. The indigenous naming system was built based on fenotyphic characters.